Preschool Adequacy and Efficiency in California Issues, Policy Options, and Recommendations - Karoly, Lynn A. (RAND Corporation, 2009)
The California Preschool Study examined gaps in school readiness and achievement in the early grades among California children and the potential for high-quality preschool to close those gaps, the use of early care and education (ECE) services and their quality, and the system of publicly funded ECE programs for three- and four-year-olds. This analysis integrates the results from the prior studies and makes recommendations for preschool policy.